Estudio de la coordinación de protecciones por métodos computarizados aplicados al sistema eléctrico “la toma (interagua)” - Fernández Flores, José Paúl (2009)
This paper discusses the electrical substation “La Toma (Interagua)”, the load flow study was conducted to determine the electrical current situation system and verify that its elements possess sufficient for normal operation contingency; reservation was made the study of short circuit to meet peak currents that circulate in each of the elements of the system in case of failure, for the right selection switches, and the respective adjustments of the elements of protection. To properly make the adjustments needed to apply the selection criteria and analyze currents in ordinary under contingency fault conditions, most importantly relay settings be undertaken so that have selectivity between them and that there is support. All elements of the system are equally important, why are protected each not only excessive flows but also of other abnormal conditions.